Peningkatan Pengetahuan Ibu Dan Anak Terhadap Infeksi Cacing Di Posyandu Sakura Puskesmas Sambutan Samarinda - Victoria Yulita Fitriani; Arjuansyah; Rahmayunitha Muriana (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2026)
Poor hygiene practices are the main factor contributing to worm infections. Worm infection is one of the most widespread diseases, affecting a large number of people around the world. In general, worm infections rarely cause serious illness, but they can lead to chronic health problems related to hygiene and economic factors. Worm infection is an endemic and chronic disease with a high prevalence that is not fatal, yet it gradually deteriorates human health, resulting in decreased nutritional status and overall public health. According to data from the World Health Organization (2019), more than 1.5 billion people (24% of the world’s population) are infected with worms.